(untitled) (World Economics and Finance Bulletin, 2021)
This article discusses the models of different countries in the transition to a market economy and gives examples from their past. The old economic relations can be gradually replaced by new market relations, forming an effective market economy. The experience of reforms shows that the evolutionary path leads to fewer social moments, is more consistent and inevitable